Comparative Gene Co-expression Network Analysis of Proviral and Antiviral Responses to Dengue Virus-2 (DENV-2) and Zika Virus (ZIKV) Infection in Human Neural Progenitor Cells (hNPCs) - J. K. Owaresat; Diptta Dey; Md. Ahashan Habib Siam; Md. Ashraful Anam; AMAM Zonaed Siddiki (PLoS ONE, 2026)
The comparative proviral and antiviral mechanisms underlying host responses to Dengue virus (DENV-2) and Zika virus (ZIKV) in neural progenitor cells remain poorly understood. In this study, we first performed weighted gene co-expression network analysis (WGCNA) on RNA-seq data obtained from 30 hNPC samples infected with DENV-2 and ZIKV to compare the proviral and antiviral responses by identifying key virus-associated modules, hub genes, and enriched pathways. A total of 4,587 genes were grouped into 12 co-expression modules. The turquoise module (867 genes) showed a strong positive correlation with DENV-2 infection, whereas the green module (479 genes) showed a strong positive correlation with ZIKV infection (r = 0.92, adjusted p < 1 × 10 ⁻ ¹²). Hub genes, including CALR in the turquoise module and HMGCS1 in the green module, were found to be associated with viral replication. Functional enrichment analysis (GO, KEGG, and Reactome) revealed that both viruses modulated virus-specific and similar proviral and antiviral pathways. Among specific proviral pathways, DENV-2 infection was primarily enriched for TGF-β signaling, whereas ZIKV infection mainly engaged host translation regulation and nucleic acid-binding pathways. Similar proviral responses included endoplasmic reticulum (ER) stress and protein-folding mechanisms. Unique antiviral responses were also observed: DENV-2 triggered p53-mediated pathways, PI3K-Akt and Hippo signaling, NF-κB signaling, oxidative stress responses, and immunoglobulin class switching, whereas ZIKV infection enriched apoptotic and inflammatory pathways. Similar antiviral responses included autophagy, ubiquitin-mediated protein degradation, and Rho GTPase effector pathways. Insights from this network-based molecular study may inform the development of potential therapeutic strategies for neurological diseases associated with DENV-2 and ZIKV.